Implementasi Pengembangan Karier Guru Pendidikan Agama Islam pada Pembelajaran Daring di Era Modern: Implementation of Islamic Religious Education Teacher Career Development in Online Learning in the Modern Era - Nurul Fitri, Ummu; Sartika; Rosdiana (ISEDU : Islamic Education Journal, 2024)
This article focuses on the implementation of teacher career development in the era of online learning. In the midst of technological advances, teacher career development is important to ensure the quality of education remains high. Digital technology-based training programs are key in strengthening teachers' pedagogical and digital competencies. This research explores the challenges faced by teachers in implementing online learning, such as limited access to technology and differences in digital skills between teachers. The method used is desk research with a deductive-inductive analysis approach to understand how teacher career development can improve the quality of learning and assist teachers in adjusting to changes in educational technology. The results show that online-based training is effective in improving teachers' technological skills, but the existing digital divide requires special attention. Therefore, teacher career development needs to include more inclusive and affordable training and address technical challenges. Recommendations from this study include the importance of policies that support increased access to technology and the development of continuous training programs to ensure the quality of education is maintained in the midst of changing times.